(untitled) - Revell, Jane (Oxford, 1993)
This book introduces and develops the strategies and skills necessary for understanding fifferent types of authentic spoken English.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Listening,Textbooks for foreign speakers,Kỹ năng nghe,Giáo trình dành cho người nước ngoài